COMPARISON OF TWO ENGLISH TEXTBOOKS USED IN INDONESIA SECONDARY EDUCATION: ENGLISH AS A SECOND LANGUAGE (CAMBRIDGE IGCSE) VS ENGLISH FOR NUSANTARA (KURIKULUM MERDEKA) - Yuyun Wachyuniah; Yanty Wirza; Karnedi Karnedi (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objectives of this research were to (1) perform a structural comparison between the English textbooks used at the secondary level in the Cambridge IGCSE (English as a Second Language) and the English textbooks in Kurikulum Merdeka (English for Nusantara); (2) analyze key differences in the expected language skill levels from English as a Second Language and English for Nusantara; (3) explore textbook materials that can facilitate students’ intercultural learning. The main sources of the study are English as a Second Language (Cambridge IGCSE) and English for Nusantara textbooks for grades 7-9. There are three main areas both explored and analyzed; the textbook organization, language skills, and how the two aspects previously mentioned support the intercultural learning of the students. The results of the research revealed that: (1) there are similarities, particularly in the development of language skills and thematic focus. However, there are significant differences in their emphasis and learning objectives; (2) in the aspect of language skills, English as a Second Language textbook provides depth in all designed texts with one language skill focus and activities that impact the language skills of the students, particularly in more formal and professional activities whereas English for Nusantara textbooks would allow the exposure to two or more languages within one unit with limited depth range; (3) in the aspects of intercultural learning, English as a Second Language emphasizes global perspective while English for Nusantara instills Indonesian cultural values and local context with gradual universal values exposure along the way